Project Planning Gedung Kedokteran Dan Farmasi Proyek UIN Maulana Malik Ibrahim Malang (Tahap 2) - Ghifari, Muhammad; Jatu, Radhia; Zettyara, Devi (Journal of Civil Engineering, 2025)
Construction project Medicine and Pharmacy Building is located in Malang Regency, precisely the project State Islamic University of Malang Maulana Malik Ibrahim Malang (Phase 2) and implemented in active lectures, it is necessary to prepare project planning so that the construction process runs according to plan. planning so that the development process runs according to the plan time, quality, and cost. Writing this thesis requires data in the form of working drawings work, work plans and requirements, unit price analysis, and BOQ. By data that has been obtained can be carried out the preparation of Work Breakdown Structurer (WBS), strategies and methods of implementation can be carried out the preparation of scheduling of work and the Implementation Budget Plan. The result of this planning, the organizational structure is arranged using a functional organizational form. (1) Site layout planning is prepared according to the results of the safety index calculation as well as traveling distance using alternative 1. management has 1 access in and out with the main place and different directors, kit is different. (2) Implementation strategies and methods using the zone method, (3) Quality plan based on Standard Operational Procedure (SOP), (4) HSE planning based on HIRRARC analysis. HIRRARC (Hazard Identification assessment and Risk Control) analysis, (5) This planning results in a project duration of 261 days (6) Budget Plan Implementation Budget Plan of Rp 121,425,418,290.58.